Chronic Thromboembolic Pulmonary Hypertension – from Diagnosis to Intervention - Kazuhiko Nakayama; Noriaki Emoto (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Chronic Thromboembolic Pulmonary Hypertension – from Diagnosis to Intervention